Investigation of the protective effect of heparin pre-treatment on cerebral ischaemia in gerbils - QingShan Ye; KeRong Hai; WenXun Liu; Yun Wang; XiaoHong Zhou; ZhenHai Ye; Xin Liu (Taylor & Francis Group, 2019)
Context: The interruption of cerebral blood circulation may cause stroke characterized by high neurological deficits (NDs) as a result of neuronal dysfunction or destruction. Heparin may exert a neuroprotective effect against cerebral ischaemia/reperfusion injury. Objective: The objective of this study was to investigate the mechanism underlying the effects of heparin pre-treatment on cerebral injury in the gerbil. Materials and methods: A total of 80 healthy Mongolian gerbils were randomly divided into four groups to establish cerebral ischaemia model by bilateral carotid artery occlusion: control (no anaesthesia and surgery), sham (no occlusion), non-anticoagulation (occlusion), and anti-coagulation treatment groups (50 IU/100 g heparin pre-treated, occlusion). Gerbils were anesthetized with 40 mg/kg pentobarbital sodium through intraperitoneal injection before operation except for the control group. Then, the ND and histopathological damage (HD) scores were determined. The percentage of tumour necrosis factor (TNF)-α- and interleukin (IL)-1β-positive cells were calculated based on immunohistochemical results. The mRNA and protein levels of caspase-9, caspase-8, FasL, and calpain were evaluated with real-time polymerase chain reaction (RT-PCR) and western blotting, respectively. Results: Compared with non-anticoagulation group, heparin pre-treatment (50 IU/100 g) delayed the onset of dyspnoea (p < 0.05), and showed a significant decrease in ND (p < 0.01), mortality rate (p < 0.05), HD (p < 0.01) and percentage of positive cells for TNF-α, IL-1β (p < 0.01) in cerebral ischaemia gerbils. Besides, the expression levels of caspase-9, caspase-8, FasL, and calpain were reduced after pre-treatment with 50 IU/100 g heparin. Discussion and conclusions: The damage caused to gerbil brain was reduced upon pre-treatment with heparin, possibly through the amelioration of neuronal cell apoptosis and expression of TNF-α and IL-1β. These findings are expected to provide a new breakthrough in the study and treatment of cerebral ischaemia.